Risk Factors Affecting the Outcomes of CT-Guided Radiofrequency Thermocoagulation of the T3 Sympathetic Nerve in the Treatment of Craniofacial Hyperhidrosis - Fan H; Xu P; Zhang E; Meng X; Xia J; Fei Y; Yao M (Dove Medical Press, 2024)
Hanrui Fan,1 Ping Xu,1 Enming Zhang,1 Xi Meng,2 Jianmei Xia,3 Yong Fei,3 Ming Yao3 1Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 2Zhejiang Sci-Tech University, Hangzhou, Zhejiang, People's Republic of China; 3Department of Anesthesiology and Pain, The First Hospital of Jiaxing, Jiaxing, Zhejiang, People's Republic of ChinaCorrespondence: Yong Fei, Department of Anesthesiology and Pain, The First Hospital of Jiaxing, 1882 Zhong-Huan-South Road, Jiaxing, 314000, People's Republic of China, Email jxfy6666662022@163.comBackground: Current studies mostly suggest that hyperhidrosis is caused by relative sympathetic hyperactivity. Sympathetic radiofrequency thermocoagulation is widely used in clinics. Previous studies have demonstrated that surgery at T3 is effective and safe compared with higher levels, so craniofacial hyperhidrosis in our hospital is selected to be treated at T3. However, some patients pursue repeat medical treatment due to an increase in hyperhidrosis at the original site after surgery. Previous studies have demonstrated the significance of Perfusion index (PI) value in the recurrence of palmar hyperhidrosis, but there is no relevant study on craniofacial hyperhidrosis.Methods: Clinical data from patients with craniofacial hyperhidrosis, who underwent T3 sympathetic radiofrequency thermocoagulation at Jiaxing First Hospital (Jiaxing, China) between January 1, 2018 and December 31, 2021, were analyzed. Recurrence in patients 1 year after surgery was recorded through a case search and telephone follow-up system that registered patient information. Clinical data were analyzed using binary logistic regression analysis to investigate risk factors associated with recurrence in patients with craniofacial hyperhidrosis 1 year after surgery.Results: Of 83 patients included in the present study, 34 (40%) experienced increased craniofacial sweating 1 year after surgery. Results of univariate logistic regression analysis revealed that computed tomography (CT) scan count, increase in pulse index (PI) at the fingertips, and differences in forehead temperature were potential risk factors for postoperative recurrence in patients with craniofacial hyperhidrosis (p< 0.2), and the results were consistent on both sides. Three potential risk factors were included in the multivariate logistic regression analysis and results revealed that the risk for recurrence was reduced by 48% (left side) and 67% (right side) for every 1 unit increase in PI value.Conclusion: A small increase in PI was an independent risk factor for recurrence of hyperhidrosis in patients with craniofacial hyperhidrosis after undergoing T3 sympathetic radiofrequency thermocoagulation.Keywords: ephidrosis, craniofacial hyperhidrosis, sympathetic radiofrequency thermocoagulation